The international role of the euro - evidence from bonds issued by non-euro area residents - André Geis; Arnaud Mehl; Stefan Wredenborg (European Central Bank (ECB), 2004)
This paper analyses the main features of the market for euro-denominated bonds issued by non-euro area residents on the basis of a new database. It shows that large private corporations from mature economies have contributed significantly to the internationalisation of the euro since 1999, more than sovereigns in transition and emerging economies, whose part was initially expected to be stronger. It confirms that the euro's international role is characterised by a strong regional focus, being most prominent in countries located in the immediate vicinity of the euro area. In particular, the paper provides ample evidence that the City of London plays a key role in the market for euro-denominated bonds issued by non-euro area residents, be it on the supply side, the demand side or as an intermediary. When it comes to demand, the paper shows that the euro's reach in the rest of the world has been more limited thus far, notwithstanding some recent interest in Asia. Finally, the paper finds evidence that the international role of the euro has, to some extent, been driven by the euro area itself, with euro area investors being significant purchasers of euro-denominated bonds issued by non-euro area residents.
Keywords: 330; Euro; Internationaler Finanzmarkt; Internationale Anleihe; Ausländer; EU-Staaten